ORGANIZATION OF ECOLOGICAL MONITORING WITH THE HELP OF GIS (Scientific journal of the Fergana State University, 2026)
The article discusses the role of geographic information systems (GIS) in the processes of monitoring and assessing the environmental situation. In particular, the advantages of using GIS technologies in priority environmental issues such as air pollution, water resource depletion, and land degradation are analyzed. The possibilities of integrating remote sensing data with GIS for spatial modeling, identifying pollution sources, establishing real-time monitoring, and improving decision-making systems are shown. The effectiveness of GIS technologies in environmental management is substantiated on the example of some scientific and practical studies carried out in Uzbekistan.